Precise Point Positioning (PPP): GPS vs. GLONASS and GPS+GLONASS with an alternative strategy for tropospheric Zenith Total Delay (ZTD) estimation - Mohammed, Jareer Jaber (2017)
Different Global Navigation Satellite System (GNSS) constellations are available these days. This has led to an increase in the number of satellites available for the user, and that presents different performance levels for the user requirements like accuracy and convergence time. However, these benefits come from different constellations that have different reference times and for some, different frequencies. At the same time, the Precise Point Positioning (PPP) has also been presented as being a position solution within a certain level of accuracy and precision. Therefore, it is important to investigate the potential benefits from the PPP with a view to using a single or multi-constellation. These investigations include accuracy, precision, and convergence time. In addition, it is important to look at the individual performance of these constellations regarding the above improvements. This will give a clear decision about adopting a single or multi-constellation. It will also provide an independent solution, for instance for the station coordinates and troposphere, and independent estimated station velocities, without additional cost. This research has been conducted in three stages. Firstly, the research begins with an evaluation of the GPS and the GLONASS (GLO) constellation geometry using a new approach for computing the cumulative dilution of precision (DOP) rather than the conventional DOP which was found to be latitude-dependent. Then it investigates the achievable station coordinate accuracy from PPP scenarios for static positioning after choosing the most appropriate PPP strategy that needs to be followed. Furthermore, the effect of different precise products (satellite orbits and clocks) on the PPP solutions and the difference between those products has been covered. It has been proven that PPP solutions can reach the same precision as a Global Double-Difference (GDD) GPS solution. Most importantly, the PPP GLO is found to be capable of producing similar precision and accuracy when compared to PPP GPS as well as the GDD GPS solution. Secondly, this research also investigates the conventional strategy (using a model for the hydrostatic component and estimating the wet component) for estimating the troposphere Zenith Total Delay (ZTD) from the PPP solutions with an evaluation of the obtained accuracy of the tropospheric ZTD from four tropospheric models. It also presents an alternative strategy (estimating both components using different mapping functions and different process noises) for estimating the tropospheric ZTD from the PPP that can give millimeters of ZTD accuracy without affecting the station coordinate estimation and without relying on any metrological data or models. Validations have been conducted for the new strategy using PPP GPS, PPP GLO and PPP GPS+GLO. Regional validation was conducted over seven consecutive days for seven weeks, using the Ordnance Survey of Great Britain (OSGB) stations in the UK, and long-term (over one year) validation was conducted using 22 stations from the OSGB. The regional and long-term validations have been conducted using three different final precise products (satellite orbits (SP3) and clocks (CLK)), which are the EMX, ESA and GFZ. A global validation using ~76 IGS stations was conducted over a different period. This was conducted in three stages, using the final EMX, final IGS and real-time IGS precise products. It was found that this approach can be used in real-time as well as in post processing without a significant difference between the results. Finally, this research has investigated the potential of using the PPP GLO for crustal motion separate to using the PPP GPS. Consistent horizontal station rates were found between PPP GPS and GDD GPS solutions. It was also concluded that it should be possible to use the PPP GLO for crustal motion, as an independent and precise solution. However, there was a bias in the orientation components of the estimated horizontal station rates between the PPP GLO and both other solutions (PPP GPS and GDD GPS), which was concluded to be a system bias rather than a strategy bias.